Academic Press dictionary of science & technology - Morris, Christopher G. (Academic Press, 1996)
Searchable CD-ROM version of Academic Press Dictionary of Science and Technology offering more than 130,000 entries, coverage of 125 fields of science, introductory essays, appendix of scientific data, over 200 illustrations, spoken pronunciations of terms, and a collection of mathematical equations and chemical structures.